Detection of Mycobacterium avium sub sp. paratuberculosis (MAP) by PCR in the faeces of dairy cattle of Chitwan, Nepal - Singh, S.; Dhakal, I. P.; Singh, U. M.; Devkota, B. (Journal of Agriculture and Forestry University, 2020)
Johne’s disease or Mycobacterium avium subspecies paratuberculosis (MAP) causes chronic granulomatous enteritis with decrease in production resulting huge economic losses with high negative impact on the livestock industry. Diagnosis of MAP is difficult due to lack of characteristics clinical signs, prolong incubation period in cultivation of MAP, and non-specific results in diagnostic tests. To the best of our knowledge there is no report on faecal culture and molecular detection of MAP in dairy cattle of Nepal. The main objective of this research was to access the herd level prevalence of Johne’s disease in the representative dairy farms of Chitwan district with the use of modern techniques as faecal polymerase chain reaction (fPCR) to know the MAP distribution in dairy cattle. A total of 265 individual dairy cattle faeces sample were collected during February 2017 to January 2018 from dairy farms of three different geographical location of Chitwan district, Nepal. Faeces were decontaminated and subjected for faecal culture as well as fPCR to have molecular detection of MAP. Findings revealed that bio-load of MAP in dairy cattle were 13.57% by faecal culture, and 16.59% by fPCR detection method. The overall prevalence of MAP in dairy cattle was detected as 16.59 % by fPCR. Likewise, IS900 PCR assay proved to be a more sensitive and reliable test than faecal culture for the detection of MAP in faecal sample of clinically suspected dairy cattle as the PCR assay was able to detect significantly (p < 0.01) more positive cases than faecal culture. Findings of this study suggests that IS900-PCR-based detection of MAP could be used as a potential diagnostic tool for rapid and effective Johne’s disease (JD) surveillance as compared with faecal culture detection method due to its advantage for JD control programs by reducing the time of definitive diagnosis from several months to a few days. This is the first molecular level of diagnostic research performed and reporting of MAP in dairy cattle of Nepal. These results will be useful in designing suitable disease control strategy for livestock industry.